MANAGEMENT OF SILVOFISHERY PONDS BASED ON PUBLIC KNOWLEDGE AND MOTIVATION IN COASTAL AREA OF PANGKEP REGENCY - Yunus, Budiman; Parawansa, Dan Basse Siang (International Journal of Research -GRANTHAALAYAH, 2020)
This study aims to analyze the management pattern of integrated mangrove ponds (silvofishery) as a form of creating an environmentally friendly ecosystem and the sustainable use of its resources. The study was conducted through direct observation of three silvofishery patterns that were developed based on the level of knowledge and motivation of the farm-pond community in the coastal area of archipelago Pangkajene District, Pangkep Regency. The research variables consist of 3 integrated management patterns, namely: 1) embankment path pattern, 2) trench path pattern, and 3) complangan pond pattern. These three patterns want to know their contribution to the production of Chanos chanos biomass, Penaeid shrimp, and Scylla sp., as a natural biodiversity and as indicator of environmentally friendly and sustainable ecosystems. Knowledge and motivation data on environmental management (silvofishery) are analyzed based on Structural Equation Modeling (SEM). Whereas the production of 3 silvofishery patterns were analyzed by Anova by SRD (0.05) test. The results showed knowledge and motivation contribute positively to the management of integrated silvofishery patterns. Furthermore, these three patterns of silvofishery contribute positively in maintaining pond production (milkfish, shrimp and crab), where the silvofishery pond pattern gives a greater influence value, and supports the realization of sustainable management of integrated ecosystems of mangroves and ponds.